Micro anatomical studies on primary and secondary bronchi in the lung of guinea fowl* - V P, SUTHAKA; USHAKUMARY, S; RAMESH, GEETHA (The Indian Journal of Animal Sciences, 2011)
The epithelium of the mucous folds of the primary and the secondary bronchi was made up of the pseudostratified ciliated columnar epithelium. Goblet cells were found in the surface epithelium of secondary bronchi. The epithelium of primary and secondary bronchi showed moderate reaction for acid and alkaline phosphatases. Lymphoid aggregations were seen in the lamina propria of the secondary bronchi. The layer of circularly arranged smooth muscle fibres in the secondary bronchi was apparently thicker than that of the primary bronchus.Â